NORMALISASI SUNGAI SONGSANG DAN PENAMBAHAN KAPASITAS TAMPUNGAN EMBUNG STANUM DALAM MENGURANGI BANJIR - Nahar Afrizal (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2022)
To fulfill raw water needs, irrigation needs, flood control, forest and land fire management and others, one of them is the construction of a reservoir or lake/situ as well as a water reservoir during the rainy season. In the Songsang River currently there is silting caused by large sedimentation. One approach to solving this problem needs to be planning for the addition of the storage capacity of the Stanum reservoir and the normalization of the Songsang river. From the results of the HEC-RAS modeling analysis, it was shown that upstream of the Stanum Embung there was flooding with varying heights (0.5m-1.5m). This is due to the relatively flat topography of the upstream riverbank. For the downstream part, there are no flood points because the contours of the cliffs are relatively high. It is necessary to model if an alternative flood inundation management is carried out with normalization and the construction of a Stanum Embung. Based on the discussion and analysis results of the HEC-RAS modeling, it shows that with the addition of the Stanum Embung storage capacity and the normalization of the upstream part of the reservoir on the Songsang River, there will be no risk of flooding.